Hubungan Antara Pola Konsumsi Diet Kariogenik Dengan Tingkat Keparahan Karies Pada Anak Usia 3-5 Tahun :Kajian Pada Paud Sapta Kemuning, Depok, Jawa Barat (Laporan Penelitian) - Aldila Paramytha N; Jeddy Jeddy (Fakultas Kedokteran Gigi Universitas Trisakti, 2021)
Background: Caries is a disease that causes from interactions of the bacteria in the oral cavity. Children aged 3 to 5 years are referred to as preschools. Most of the children susceptible to dental and mouth problems because they do not have the behavior or habits to maintain dental and oral hygiene so they still need other people, and they have a habit of eating foods that are cariogenic. The patterns of diet cariogenic consumption that associated with the occurrence of caries depends on the type of food consumed and the frequency of eating. Objective: To find out the relationship between the patterns of diet cariogenic consumption and the severity of caries in children aged 3-5 years old in PAUD Sapta Kemuning, Depok, West Java. Method: Observational analysis method is used in this research on 56 subjects aged 3-5 years. The children were examined by the supervisor and the parents are given a questionnaire in the form of Food Frequency Questionnaire (FFQ). Result: Out of total 56 research subjects obtained, most students had a moderate level pattern of diet cariogenic consumption had a high severity of caries. Spearman correlation test results showed p value of 0.01 (p <0.05) and correaltion coefficient of 0.343. Conclusion: There is a relationship between the patterns of diet cariogenic consumption and the severity of caries in children aged 3-5 years old in PAUD Sapta Kemuning, Depok, West Java.